(untitled) (The Research of Medical Science Review, 2024)
Energy problems and environmental destruction are the main issues facing today's world. The use of green energy is the perfect option for all of these issues. Edible and non-edible oils are green energy options that can be used for the production various hydrocarbons and chemical. In this research, the conversion of the used edible oil over a metal oxide catalyst into various liquid hydrocarbon compositions was analyzed and compared. In a batch reactor, reaction parameters such as metal oxides like (ZnO, Al2O3 and ZrO2), catalyst quantity, temperature, residence time, heating intensity, and stirring intensity were studied. Under a controlled temperature regime, each conversion analysis was conducted. The powdered samples of the catalysts ZnO, Al2O3 and ZrO2 were analyzed using XRD, EDX, and Nitrogen Adsorption Isotherms characterization techniques. Liquid hydrocarbons were studied using GC-MS. Various physical and chemical properties of liquid hydrocarbons have been tested to verify the caloric content, stiffness, flash point and kinematic viscosity of liquid hydrocarbons. Using different percent of ZnO catalyst, catalytic cracking of used cooking oil was carried out in the batch reactor at 400 ° C to 500°C. Catalytic cracking was carried out at 330°C to 430°C for Al2O3 and catalytic cracking was carried out at 400°C to 500°C for ZrO2. It was funded that 81% of conversion occurs at 450°C, for 60 mints at a heating rate of 10°C/min and 4wt% of ZnO loading. 71% conversion was observed at 390°C with 8wt% of Al2O3 catalyst for 60 mints at a heating rate of 5°C per mint. For ZrO2, 81% conversion Occur at 475°C using 4wt% of the ZrO2 catalyst for 60 mints at a heating rate of 10°C per mint.